Estudo dos impactos causados no rendimento pelos microrganismos na etapa de fermentação - Oliveira, Gabriel Martins (2019)
The aim of this paper is to review the literature on the impacts without fermentative yield of ethanol production by microorganism. The methodology used was a bibliographic study, as research source were used: Internet documents, scientific articles available on scientific platforms and handouts for alcohol manufacture. The results were qualitative, being defined and approximated or researched by observation, fostering discussions about: ethanol production, alcoholic fermentation, microbial contamination, conditions that cause contamination, contaminating microorganisms, performance and forms of contamination control. Thus, through the comparative debate of the data, it is noted whether the control of factors such as: pH, temperature, osmotic pressure and °Brix; directly and indirectly influences the proliferation of microorganisms that brings harm to the fermentation and consequently to the fermentative yield.